2011
DOI: 10.1371/journal.pone.0025002
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Based Recognition of Familiar and Related Conspecifics: A First Test Conducted on Captive Humboldt Penguins (Spheniscus humboldti)

Abstract: Studies of kin recognition in birds have largely focused on parent-offspring recognition using auditory or visual discrimination. Recent studies indicate that birds use odors during social and familial interactions and possibly for mate choice, suggesting olfactory cues may mediate kin recognition as well. Here, we show that Humboldt penguins (Spheniscus humboldti), a natally philopatric species with lifetime monogamy, discriminate between familiar and unfamiliar non-kin odors (using prior association) and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 26 publications
(33 reference statements)
2
50
0
Order By: Relevance
“…Coffin et al (2011) found that Humboldt penguins were able to differentiate between kin and non-kin using odours. Other studies on Procellariiforms suggest similar abilities in the penguin's closest relatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffin et al (2011) found that Humboldt penguins were able to differentiate between kin and non-kin using odours. Other studies on Procellariiforms suggest similar abilities in the penguin's closest relatives.…”
Section: Resultsmentioning
confidence: 99%
“…and F.B., unpublished results). Interestingly, work by Coffin et al (2011) suggested that Humboldt penguins (Spheniscus demersus) could recognize kin using olfactory cues alone suggesting a non-foraging role for olfaction in penguins. This should not be surprising, since the penguins' closest relatives, the Procellariiforms (Hackett et al, 2008), appear to use olfaction in a social context (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kin recognition through olfactory signals has also been recently investigated in other species including Humboldt penguins ( Spheniscus humboldti ) (Coffin et al, 2011), zebra finches (Caspers et al, 2013; Krause et al, 2012), and European storm petrels (Bonadonna and Sanz-Aguilar, 2012). In these experiments, the birds themselves were asked to discriminate between odors coming from related and non-related individuals, and while all were able to discriminate between kin and non-kin individuals, the behavior was dissimilar according to the species.…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 99%
“…For instance, in species as diverse as humans, bank voles (Myodes glareolus), sand lizards (Lazerta agilis) and house mice (Mus musculus), females prefer the scent of MHC-dissimilar males [6,10,11,13]. In birds, although European storm petrels (Hydrobates pelagicus), Humboldt penguins (Spheniscus humboldti) and zebra finches (Taeniopygia guttata) can discriminate kinship based on odour cues [14][15][16] and the scent secretions of black-legged kittiwakes (Rissa tridactyla) covary with MHC similarity [17], the ability of birds to assess MHC similarity using olfactory cues has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%